Redescription of Armillipora Quate (Diptera: Psychodidae: Psychodinae) with a new species from Bolivia - JeŽek, Jan; OboŇa, Jozef; LE Pont, Franↅois; Maes, Jean-Michel; Martinez, Eddy (Zootaxa, 2020)
The former monotypic genus Armillipora Quate, known only from Costa Rica and Panama, is redescribed, including the type species A. selvica Quate, this time collected on the Caribbean side of Nicaragua, RAAN department, and illustrated based on male morphological characters. The male of a new species, A. suapiensis sp. nov., from Bolivia, La Paz department, is described here and also figured.
Keywords: Bolivia; Animals; Bolívie; mužské pohlaví; Psychodidae; Male; Diptera; zvířata